Herbie Jones and the dark attic - Kline, Suzy.; Williams, Richard (New York : Scholastic Inc, 1992)
Herbie's friend Ray and some classmates in his fourth-grade reading group help him adjust when he moves into a new bedroom in the attic.
Keywords: Fear; Schools